Paul and Isaiah's servants : Paul's theological reading of Isaiah 40-66 in 2 Corinthians 5:14-6:10 /: Paul's theological reading of Isaiah 40-66 in 2 Corinthians 5:14-6:10. (©2007) - Unknown
No abstract available